Tuberculosis, vulnerabilities, and HIV in homeless persons: a systematic review - Gioseffi,Janaína Rosenburg (2022)
ABSTRACT OBJECTIVE Analyze, systematize, and compile social, individual, and programmatic vulnerability factors associated with tuberculosis and HIV in homeless persons. METHODS This is a systematic literature review assessing quantitative studies, published between 2014 and 2020, on the prevalence of tuberculosis in homeless persons. Our review grouped studies according to vulnerabilities, followed the PRISMA recommendation guide, and used the Joanna Briggs Institute Critical Appraisal tool for bias analysis. RESULTS Of the 372 publications found, 16 were selected according to our eligibility criteria. In total, 10 studies assessed tuberculosis and HIV. The most commonly described factors for individual, social, and programmatic vulnerability were drug use, HIV coinfection, and tuberculosis treatment failure, respectively. The literature also claims that average homelessness length related to a higher frequency of tuberculosis and latent tuberculosis infection. CONCLUSION All reviewed studies described how homeless persons suffer with stigma and dehumanization, which are important barriers to their access to health services. Homelessness enhances the risks of chronic and infectious diseases and prioritizes issues which are more pragmatic for the maintenance of life, such as safety and food, to the detriment of health. The results can be used to support hypotheses for future research and to reinforce and direct existing public health and social policies to cope with tuberculosis and HIV in homeless persons.